Análise, projeto e implementação de um retificador Boost monofásico com alto fator de potência e comutação ZCS das chaves - Borges, Fabrício Alves (2013)
In order to reduce switching losses and electromagnetic interference (EMI), as well as to attend harmonic standards, such as the IEC61000-3-2, in switch-mode power supplies, this work presents a high power factor Boost rectifier with a turn-on turn-off zero-current switching (ZCS) cell. The proposed converter incorporates the most desirable properties of conventional PWM and soft-switching resonant techniques through the substitution of the typical PWM cell found in classics power converter structures by the presented ZCS cell. A ZCS operation of all active switches is achieved without additional current and voltage stress on the switches. The input current shaping is achieved with average current control, performing the power factor correction with low total harmonic distortion (THD) of current. This work presents the principle of operation, theoretical analysis, a design example, simulation and experimental results obtained from a 450 W laboratory prototype, in order to corroborate with the theoretical analysis.